Cloud Computing and Data Security Challenges: A Nepal Case - Yadav, Birendra Prasad (Journal of Economics and Management, 2024)
When it comes to storing and accessing data, cloud computing provides an alternative option for users of computers and mobile devices. Nepal has a lot of problems with cloud computing and protecting data. Data security in the cloud and cloud computing are topics the author is investigating. The investigation is carried out using the content analysis method. According to the research, cloud computing is crucial for the storage, regulation, and accessibility of data in Nepal. Additionally, Nepal is a developing nation. The data security issue is real because it has lacked the necessary technological know-how, financial resources, human resources with the necessary skills, and a large digital divide. Security in the cloud is mostly concerned with storage, virtualization, and networks. Users and providers of cloud services are primarily concerned in virtualization, which enables numerous users to share a single physical server. Data transmitted by remote virtual equipment is a prime target for assaults on cloud networks. Security, storage, data center operations, pricing, service level agreement, location, integrity, access, segregation, breaches, and confidentiality are just a few of the cloud computing issues that Nepal is clearly encountering. Nepal, like many other developing nations, should begin to make use of its own servers, satellites, and data centers or banks for communication and storage.